PENGARUH BAHAN BAKAR PREMIUM DENGAN SHELL TERHADAP KINERJA MESIN MOTOR KMHE â€œHAIZUMâ€ - Ubaidillah, Achmad Wildan (UNIVERSITAS ISLAM MALANG, 2020)
The need for transportation will have an impact on the number of motorized vehicles and on fuel consumption. The consumption of high fuel oil will automatically increase the budget for transportation, so that the mixing of fuel oil aims to get better combustion, one of which is mixing with a premium shell. At this time the researchers conducted a study relating to the comparison of the performance produced and the extent of the mileage produced by Premium and Shell fuels, from this study is expected to provide accurate information about the use of appropriate fuels, researchers also use motors KMHE Haizum as a test material for performance and maximum mileage produced from both types of fuel. With the hope it can be applied to various types of motorcycles. The method used in this study uses quantitative descriptive methods and direct field studies so that the data obtained is truly accurate and can be trusted. For the hypothesis in this study is which fuel has better performance, and which distance is farthest by using Premium fuel, Shell, and a mixture of the two fuels. The test results and the calculation of the use of specific fuels in energy-efficient car vehicles